Factors Associated with Depressive Symptoms in Young Adults with Coronary Artery Disease: Tehran Heart Center's Premature Coronary Atherosclerosis Cohort (THC-PAC) Study - Seyed Hesameddin Abbasi; Seyed Ebrahim Kassaian; Saeed Sadeghian; Abbasali Karimi; Soheil Saadat; Flora Peyvandi; Arash Jalali; Tahereh Davarpasand; Shahin Akhondzadh; Nazila Shahmansouri; Masoumeh Lotfi-Tokaldany; Maryam Amiri Abchouyeh; et al. (Iranian Journal of Psychiatry, 2016)
Objective: Depressed coronary artery disease (CAD) patients may experience a poorer prognosis than non-depressed patients. The aim of this study was to find the associated factors for depressive symptoms in young adults with CAD.